Brain metastases at the time of presentation of non-small cell lung cancer: a multi-centric AERIO analysis of prognostic factors - Jacot, W; Quantin, X; Boher, J-M; Andre, F; Moreau, L; Gainet, M; Depierre, A; Quoix, E; Le Chevalier, T; Pujol, J-L (British journal of cancer, 2001)
A multi-centre retrospective study involving 4 French university institutions has been conducted in order to identify routine pre-therapeutic prognostic factors of survival in patients with previously untreated non-small cell lung cancer and brain metastases at the time of presentation. A total of 231 patients were recorded regarding their clinical, radiological and biological characteristics at presentation. The accrual period was January 1991 to December 1998. Prognosis was analysed using both univariate and multivariate (Cox model) statistics. The median survival of the whole population was 28 weeks. Univariate analysis (log-rank), showed that patients affected by one of the following characteristics proved to have a shorter survival in comparison with the opposite status of each variable: male gender, age over 63 years, poor performance status, neurological symptoms, serum neuron-specific enolase (NSE) level higher than 12.5 ng ml –1 , high serum alkaline phosphatase level, high serum LDH level and serum sodium level below 132 mmol l −1 . In the Cox’s model, the following variables were independent determinants of a poor outcome: male gender: hazard ratio (95% confidence interval): 2.29 (1.26–4.16), poor performance status: 1.73 (1.15–2.62), age: 1.02 (1.003–1.043), a high serum NSE level: 1.72 (1.11–2.68), neurological symptoms: 1.63 (1.05–2.54), and a low serum sodium level: 2.99 (1.17–7.62). Apart from 4 prognostic factors shared in common with other stage IV NSCLC patients, whatever the metastatic site (namely sex, age, gender, performance status and serum sodium level) this study discloses 2 determinants specifically resulting from brain metastasis: i.e. the presence of neurological symptoms and a high serum NSE level. The latter factor could be in relationship with the extent of normal brain tissue damage caused by the tumour as has been demonstrated after strokes. Additionally, the observation of a high NSE level as a prognostic determinant in NSCLC might reflect tumour heterogeneity and understimated neuroendocrine differentiation. © 2001 Cancer Research Campaign